CGIAR Platform for Big Data in Agriculture - Plan of Work and Budget 2017 - CGIAR Platform for Big Data in Agriculture (CGIAR Platform for Big Data in Agriculture, 2017)
CGIAR Platform for Big Data in Agriculture - Plan of Work and Budget for 2017